Epidemiology and clinical features of community acquired pneumonia: hospital based study - Lamb, Avinash; Patil, Amol Harinathrao (International Journal of Research in Medical Sciences, 2018)
Background: Community acquired pneumonia (CAP) is an infection affecting a significant proportion of population from all age groups across the globe with considerable morbidity and mortality. There is a need for data from various parts of India to better understand the epidemiology of CAP. Present study is an attempt to present the relevant data from a tertiary care hospital in Rajkot, Gujarat during the study period. Methods: This observational prospective descriptive study was done during November 2014 to April 2016 at Department of TB and chest diseases, PDU Hospital at Rajkot in Gujarat. 50 patients with clinical features suggestive of CAP were enrolled. Male and female patients (above age of 12 years) admitted to TB and Chest ward or patients on OPD basis were selected for the study. The diagnosis of CAP was mainly clinical with some assistance from radiological picture. All patients were thoroughly examined particularly with regards to detailed history, clinical examination, predisposing factors and associated co-morbid conditions. Sputum examination-gram stain and culture sensitivity was done in all patients, where sputum was available. Sputum examination for acid fast bacilli (AFB) by Ziehl Nelson staining technique was done. Age and sex distribution of patients, microorganisms isolated and the clinical features were described and analyzed. Results: The mean age was 38.38±17.41 (SD) years. Male patients were 34 (68%) and female patients were 16 (32%). Male to female ratio was 2.1:1. In this study, 47 (94%) patients were admitted in the hospital for the management and 3 (6%) patients were treated on the OPD basis. Fever and cough were most common symptoms whereas dull note on affected side and crepitations were the commonest signs elicited. In this study, the most common predisposing factor was smoking which accounted for 20 (40%) patients. The most common lobe involved was Left Lower lobe accounting for 20 (40%) patients and least common lobe involved was left upper lobe accounting for 2 (4%) patients. Streptococcus pneumoniae was the most common organism isolated in 8 (16%) patients and second common organism was Klebsiella isolated in 7 (14%) patients. Conclusions: Males, especially smokers were more commonly affected and Streptococcus pneumoniae was the most common organism isolated. The study gives the hospital based data from the region regarding epidemiology and clinical features of community acquired pneumonia.